2013
DOI: 10.1177/1362168812460814
|View full text |Cite
|
Sign up to set email alerts
|

Incidental vocabulary learning in classroom communication tasks

Abstract: This study investigated the ways in which two groups of four adult learners of English as a second language (ESL) responded to unfamiliar words they encountered in four communication tasks and the effect that different levels of engagement with these words (including negotiation of form and meaning) had on subsequent recall of word meaning. Of the four tasks, two were information gap tasks and two were opinion gap tasks. The results showed a strong task type effect on both the amount and type of negotiation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 38 publications
3
45
0
Order By: Relevance
“…It may be that frequent encounters with unknown or partially known words in a single text leads to an immediate gain in vocabulary knowledge, but it is the use of these words by the students after reading that contributes to more durable long-term gains. Research has indicated that using words in speech or writing can have a positive effect on vocabulary learning gains (Joe, 1998;Newton, 2013). After reading, some of the frequently encountered words might be used and retained, while others might not be used and are forgotten.…”
Section: Pedagogical Implicationsmentioning
confidence: 99%
“…It may be that frequent encounters with unknown or partially known words in a single text leads to an immediate gain in vocabulary knowledge, but it is the use of these words by the students after reading that contributes to more durable long-term gains. Research has indicated that using words in speech or writing can have a positive effect on vocabulary learning gains (Joe, 1998;Newton, 2013). After reading, some of the frequently encountered words might be used and retained, while others might not be used and are forgotten.…”
Section: Pedagogical Implicationsmentioning
confidence: 99%
“…In TBLT, these gains are often discussed in terms of measuring changes in complexity, accuracy, and/or fluency (CAF; for a thorough review of CAF measures see Housen, Kuiken, & Vedder, 2012; for an empirical example see Kim & Tracy-Ventura, 2013). Task-based manipulations with the goal of promoting L2 development have focused on instruction (e.g., De Ridder et al, 2007), task type(s) (e.g., Newton, 2013;Révész & Han, 2015), task complexity (e.g., Nuevo, Adams, & Ross-Feldman, 2011), interlocutor (e.g., Kim & McDonough, 2008), and mode (most often FTF as compared to SCMC; e.g., Baralt, 2014). Empirical research has found these task-based manipulations to promote the development of L2 accuracy, at least for lexis and grammar.…”
Section: Tblt and L2 Developmentmentioning
confidence: 99%
“…The results of this study, along with several other studies (e.g., Tian & Macaro, 2012), suggest that intentional FFI is superior to incidental vocabulary exposure in classroom contexts. However, note that a number of studies have shown that a limited amount of vocabulary can also be learned incidentally (e.g., Bisson, van Heuven, Conklin, & Tunney, 2014;Gablasova, 2014;Liu & Todd, 2016;Newton, 2013;Pellicer-Sánchez, 2016).…”
Section: Form-focused Instructionmentioning
confidence: 99%